Adherence to Guidelines among Italian Urologists on Imaging Preoperative Staging of Low-Risk Prostate Cancer: Results from the MIRROR (Multicenter Italian Report on Radical Prostatectomy Outcomes and Research) Study. (15th May 2012) - Simonato, Alchiede; Varca, Virginia; Gacci, Mauro; Gontero, Paolo; De Cobelli, Ottavio; Maffezzini, Massimo; Salvioni, Roberto; Carini, Marco; Decensi, Andrea; Mirone, Vincenzo; Carmignani, Giorgio
Abstract : Objective . A number of evidence-based guidelines for diagnosis and management of prostate cancer have been published. The aim of this study is to evaluate the adherence of Italian urologists to the guidelines concerning the preoperative imaging staging of prostate cancer. Methods . In October 2007 a multicentric observational perspective study called Multicentric Italian Report on Radical prostatectomy Outcome and Research (MIRROR) was started in 135 Italian urology centers. Recruitment was closed in December 2008 and 2, 408 cases were collected. In this paper we have taken into consideration all examinations carried out for preoperative imaging staging, evaluating compliance with the recommendations in the American Urological Association (AUA) and European Association of Urology (EAU) guidelines. Results . Five hundred sixty-seven (53.34%) patients were not managed according to the EAU guidelines concerning T-staging, 545 (51.27%) concerning N-staging and 757 (71.21%) concerning M-staging. According to AUA guidelines, we also analyzed patients with a Gleason grade of biopsy specimens of 7: 238 (57.35%) of these patients had undergone testing for T staging, 244 (57.35%) for N-staging and 322 (77.60%) for M-staging. Conclusions . The compliance of Italian urologists with the guidelines is low, leading to an inappropriate increase in cost of care and unnecessary anxiety for the patients.